Tocilizumab combined with short-term high-dose glucocorticoids for rapid disease activity control and glucocorticoid reduction in adult-onset Still’s disease: a single-center retrospective study - Zhong, Shi-Lei; Lei, Yan-Ping; Zhou, Li-Xuan; Niu, Ai-Xia; Liu, Bo; He, Yong-Long; Yang, Qi-Bin (Frontiers in Immunology, 2026)
ObjectivesThis study aimed to evaluate the effectiveness of tocilizumab (TCZ) combined with short-term high-dose glucocorticoids in rapidly controlling disease activity and reducing glucocorticoid use in patients with adult-onset Still’s disease (AOSD).MethodsIn this single-center retrospective study, all patients meeting the inclusion criteria were enrolled. Patients receiving short-term high-dose glucocorticoids (5 mg/kg/day for 3 days) with TCZ (400 mg every 4 weeks) were assigned to the TCZ group, while those receiving standard-dose glucocorticoids (1 mg/kg/day) without TCZ formed the non-TCZ group. Efficacy was evaluated based on laboratory data, clinical and Pouchot scores. Glucocorticoids -retention rate was estimated by the Kaplan-Meier method.ResultsFifty patients (11 men, 39 women) were included (19 in the TCZ group and 31 in the non-TCZ group). The TCZ group had a higher incidence of skin rash (100% vs 58.1%, P = 0.003) and sore throat (84.2% vs 29.0%, P < 0.001). Over the follow-up period, inflammatory markers (CRP, ESR, SF), liver enzymes (AST, ALT), and WBC counts significantly declined in the TCZ group (P < 0.05). Remission rates were higher in the TCZ group at months 1 (63.2% vs 9.7%), 3 (88.9% vs 20.0%), and 6 (83.3% vs 25.9%) (P < 0.001). Despite a higher initial glucocorticoid dose, no significant differences in subsequent doses were observed between groups. By 36 months, the TCZ group showed a significantly higher glucocorticoid discontinuation rate (77.0% vs 30.9%, P = 0.0046). TCZ treatment was also associated with improved liver function indicators and reduced liver injury (10.5% vs 32.3%).ConclusionTocilizumab combined with short-term high-dose glucocorticoids may provide rapid disease control and facilitate glucocorticoid tapering in AOSD. More prospective studies are needed to confirm these findings.